(untitled) (Central Asian Journal of Medical Sciences, 2017)
Objectives: Up to one third of epilepsy patients have an unsatisfactory treatment with antiepileptic drugs (AEDs), but advance in neuroimaging, neurophysiologic investigation and treatment modalities have substantially improved the approaches and understanding of intractable childhood epilepsy. Methods: Journal papers, reports, books and government publications on epilepsy treatment were collected and reviewed in chronological order. Results: There are approximately more than 15 newer AEDs developed since 1990, highlighted by the novel mechanism of action with minimal adverse effect, thus they have been frequently used for those who are unresponsive to conventional AEDs. Non-pharmacologic therapies including diet therapy, epilepsy surgery, and neuromodulatory treatment are also effective and should be considered early in the disease course. Diet therapy began to reemerge in mid 1990s, and studies with large data collection allowed to overcome major concerns; its side effects, difficult compliance and doubts on efficacy. And more liberal forms of the diet therapy were introduced to benefit adults and patients in developing counties, where strict supervision is unavailable. The surgical treatment has become increasingly more valuable and it is now accepted for the management of drug resistant focal epilepsy due to major advances in presurgical investigation methods, and surgical techniques. Conclusions: The timely assessment of children with drug-resistant epilepsy and active application of advanced treatment modalities were necessary to prevent the effect of uncontrolled seizures on cognitive and behavioral development.